Managing clinical trials in Asia: Issues, threats, opportunities and approaches - Rahman, Sayeeda; Majumder, Md Anwarul Azim (South East Asia Journal of Public Health, 2013)
Abstract not available DOI: http://dx.doi.org/10.3329/seajph.v2i2.15961 South East Asia J Public Health | Jul-Dec 2012 | Vol 2 Issue 2 | 80-84